EFFECT OF BIOSTIMULANT AND MICRONUTRIENT ON EMERGENCE, GROWTH AND QUALITY OF ARABICA COFFEE SEEDLINGS - Ferreira, Bruno Costa; Lima, Sebastiao Ferreira de; Simon, Cátia Aparecida; Andrade, Maria Gabriela de Oliveira; de Ávila, Jorgiani; Alvarez, Rita de Cássia Félix (Coffee Science - ISSN 1984-3909, 2018)
The micronutrients and biostimulant use can promote root, shoot and seedling growth. The aim of this work was evaluated the micronutrients and biostimulant application effects on arabica coffee seedling development. The experimental design was a randomized block in factorial 5 x 3, with four replicates. Five cultivars of arabica coffee (Topázio, Catuaí Amarelo, Catuaí Vermelho 99, Catuaí Vermelho 144 and Catiguá) cultivated in green house, combined with biostimulant (Stimulate®), of micronutrients (Mo+Co) and control. 150 days after sowing the plants was evaluated. The higher seed germination velocity (0.10) was obtained with micronutrients and biostimulant. The higher height of plant, 8.88 cm, was attained with biostimulant on Catuaí Amarelo. Catuaí Amarelo and Vermelho obtained higher number of leaves (4.5) with biostimulant use and the Catuaí Amarelo (4.38) with micronutrients use. In Catuaí Amarelo was attained higher shoot dry mass and leaf area with biostimulant use, reach 1.69 g and 19.55 cm2, respectively. The higher root dry mass values (0.76 g) and Dickson quality index (0.47 and 0.48) was attained with micronutrients use to the Catuaí Amarelo e vermelho cultivars. Seedling development of Catuaí Amarelo was benefited with Stimulate® application and the cultivar Topázio did not get positive development with Stimulate® and micronutrients application.